Unravelling the role of interfacial chemistry evolution in the kinetics of zinc insertion into chevrel phase - Lee, Boeun; No, Woo Joo; Oh, Si Hyoung (ELSEVIER, 2020)
The insertion kinetics of the multivalent cations into an intercalation host is conventionally understood primarily focused on the ion migration and charge redistribution properties through the bulk solid framework. Here we show that the intercalation kinetics of zinc ions into a Mo6S8 Chevrel phase is critically dependent on the interfacial chemistry evolution associated with changes in the electrolyte pH and the formation of zinc hydroxide sulfate (ZHS) during the early cycles. The sluggish initial insertion process with a hydroxyl surface groups on Mo6S8 causes a concurrent intercalation of zinc ions into the inner and outer ring vacancy sites, leading to the temporary coexistence of three reaction phases. On the contrary, characteristic two-step, two-phase reactions associated with the sequential occupation of each vacancy site are observed after the electrolyte pH change induces ZHS deposit in the interface, which eliminates hydroxyl adsorption layer on the surface, and promotes the intercalation kinetics of zinc ions. This study provides valuable insight into insertion of multivalent cations into Chevrel phase, which often exhibits a cryptic kinetic dormancy during the initial cation intercalation stages.
Keywords: CLUSTER CHALCOGENIDES MO6X8; RECHARGEABLE MG BATTERIES; SMOLUCHOWSKI EQUATION; ALUMINUM IONS; MAGNESIUM; INTERCALATION; CATHODE; MO6S8